The Yankee Plague : Escaped Union Prisoners and the Collapse of the Confederacy - Foote, Lorien, 1969- (Book collections on Project MUSE., 2017)
During the winter of 1864, more than 3,000 Federal prisoners of war escaped from prison camps into South and North Carolina. In this look at Union soldiers' flight for freedom in the last months of the Civil War, Lorien Foote reveals connections between the collapse of the Confederate prison system, the large-scale escape of Union soldiers, and the unravelling of the Confederate States of America.